Management and prioritization of barriers to land integration in the field of agricultural mechanization in Jiroft –Iran - Mohammad Zamani, Davood (Eximia, 2021)
Existence of small and scattered agricultural lands in Jiroft located in southeastern Iran, as an agricultural area and lack of effective use of modern technology, to conduct a study with the aim of managing and prioritizing the factors of effective reduction in land reduction as an obstacle to progress in mechanization, By providing solutions for agricultural development, appropriate. The statistical population of the research, including all land users, agricultural experts and sample members, have been purposefully selected from among them according to the objectives and questions of the research. The research instrument was a questionnaire, that its validity reviewed and corrected using a group of academic researchers and experts in the field of agricultural land fragmentation. Hierarchical analysis to prioritize the effective factors with Expert Choice software revealed that social, economic, environmental and structural factors contribute 39%, 30%, 17% and 14%, respectively. The results showed that the criteria of family disputes and inheritance related to social factors are the most important barriers in this area in the region. For develop Jiroft mechanization; It is recommended to pay attention to the role of village elders in mediating and solving problems, amending the inheritance law, implementing an optimal cultivation pattern ,giving financial credit for the modernization of agricultural implements.